Upaya Meningkatkan Kemampuan Berbicara Dengan Menggunakan Media Boneka Tangan Pada Anak Usia Dini - Silvia Rizki; Melvi Lesmana Alim (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by the low level of children's fine motor skills at Az-Zahra Kindergarten, Perhentian Raaja District, Kampar Regency. For this reason, a concrete application is needed to be able to find the right way regarding children's fine motor skills, namely the application of methods to improve children's speaking through the hand puppet method in early childhood. This study aims to determine whether through the hand puppet method the application of speaking can improve fine motor skills in early childhood. This type of research is class action research which is an observation of learning activities in the form of an action, which deliberately appears and occurs in a class together with a total of 12 children consisting of 6 boys and 6 girls. Data collection techniques in this study are observation and documentation. The data analysis technique used in this study is percentage. From the results of class action research and discussion as described, it is concluded that the results of this research are that the hand puppet media method can improve children's fine motor skills at Az-Zahra Kindergarten. Children's fine motor skills can be seen from the pre-cycle in the “Not Developing” criteria, namely 9 children or 75%. After the action in cycle I, namely through the hand puppet method, there was an increase, namely reduced to Ianak or 8.33%. In the “Starting to Develop” criteria, the pre-cycle increased by 3 children or 25% and increased again in cycle II to I or 8.33%. In the criteria “Developing as expected” there was not a single child in this criterion, increasing to 8 children or 66.7%, and increasing again in cycle II to I child or 8.33%. In the criteria “Developing Very Well” increased from pre-cycle no, in cycle I also no and increased again in cycle II to 10 children or 83.33%. Keywords: Speaking Ability, Hand Puppet Media, CAR